MRI’s Diagnostic Reliability in Cervical Cancer Screening Detecting Cancer using Magnetic Resonance Imaging is a Reliable Method (MRI) A Single Center Study - Iqbal Ahmad, Erum Habib, Muhammad Nabi (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: to evaluate the diagnostic efficacy of magnetic resonance imaging (MRI) for cervical cancer detection in patients with cervix carcinoma who had received a clinical diagnosis. Study Design: A Single Center Study Place and duration Department of Radiology Qazi hussain ahmad medical complex Nowshera from january 2018 to December 2019. Methods: In all, 75 individuals between the ages of 31 and 62 with clinically suspected cervical cancer were recruited in this research. After obtaining written agreement, extensive patient demographic information was gathered, including their age, place of residence, socioeconomic status, co-morbidities, and clinical presentation. An MRI of the pelvis was performed on each patient to find the malignancy. Histopathology was used as the standard. Results: Patients’ ages ranged from 31 to 41 years for 15 (21%) patients, 42 to 52 years for 26 (34%) patients, 53 to 63 years for 21 (28%) patients, and beyond 61 years for 13 (18%) patients. The most prevalent symptom, post-menopausal bleeding, was seen in 32 (42%) patients, followed by atypical vaginal bleeding in 25 (34%) patients, foul-smelling watery discharge in 18 (24%) patients, and pelvic discomfort in 15 (21%) patients. By MRI, 53 patients (71%) had positive results, while 22 patients (29%) had negative findings. By histological examination, 56 patients (75%) had positive findings, while 19 patients (24%) had negative. The diagnostic accuracy of MRI was 90%, 87, 96, 74%, and 87%, respectively. Sensitivity, specificity, PPV, and NPV were also high. Conclusion: For cervical cancer diagnosis, magnetic resonance imaging is a beneficial diagnostic technique. Keywords: Cervical Carcinoma, Accuracy, Magnetic Resonance Imaging